Zur Bodengestalt des Indischen Ozeans: Bericht über den gegenwärtigen Stand der Forschung - Stocks, Theodor (ERDKUNDE, 1960)
Similar to the Atlantic ocean floor, also the Indian ocean floor shows a central ridge with a longitudinal extension of some 13 000 km and with its major axis trending S/N; it takes its origin in the neighbourhood of the Gaussberg in the South (Antarctica) and, while varying its course from SE to NW and SW to NE, it extends with differing width as far as beyond the equator; here it splits into two bran ches : the Chagos-Laccadive ridge, which joins the Indian peninsula in the latitude of Goa, and the so called Carlsberg (north-western Indian-) ridge, which, after having described a wide curve via Sokotra, turns to NE until it becomes merged in the Asiatic continent in the region of the Indus-delta, apparently in the Khirdar mountains. There are no soundings available proving the existence of the central part of the ridge between the 30th° and the 20th° S; the particular features proper to the distribution of the bottom water suggest, however, the presence of this part of the ridge. The Indian ridge divides into several remarkable branches. Between the Kerguelen islands -up to this point it is named the Kerguelen-Gaussberg ridge - and the Crozet islands there is, f. i., a ridge interrupted by a depression at two places in about 60° E; following its plateau like widening, we find the Crozet ridge, which trends W, interrupted by a passage near the Agulhas shelf at a depth of abt. 4500 m, then follows the Madagscar ridge with a northern trend and apparently without any depressions or passages within a depth range of 4000 m, and at last, another ridge to the NE which so far has not been given a name; this branch ends without any continuation S of Rodriguez island, and separates the Madagascar basin from the South-West Indian basin. The gap between the Atlantic and the Indian ridge in 50° S, 30° E is generally known. As a counterpart to the Atlantic-Indian ridge, we may regard the apparently very broad plateau-like elevation which begins in the region between the Kerguelen islands and the group of the St. Paul- and New-Amsterdam islands ; this elevation extends to the East until it reaches the eastern border of the Indian ocean, viz. the system of the Tasman- and the Macquarie ridges. It has a passage in about 120° E, that has recently been confirmed by soundings and that is of great importance to the distribution of the bottom water. Several smaller branches of the South Indian ridge have altered the conception, held heretofore, of the bottom configuration of the Indo-Australian basin, which was considered to be characterized by the absence of any sort of bottom elevations. Thus we now find rise like connections in about 40° S, 110° E in the direction of Cape Leeuwin (South-Western Australia), in 35° S in the direction of Perth, and, at last, in 25° S, 100° E in the direction of the Cape Cuvier ridge (Western Australia). As a new feature in the bottom configuration of the NE part of the Indian ocean and as a counterpart to the Lacca dive ridge we may consider the ridge that comes from the Nicobar islands and in about 90° E trends S; whether or not this ridge may be connected to the respective branch of the South Indian basin within the depth range of 4000 m, may be left out of account for the present. The conception with regard to the structure of ridges and rises or sills respectively in the region of the Keeling-(Cocos-) and Christmas islands - how incomplete in its details it ever may be - nevertheless permits to draw the conclusion that the water of the Sunda trench system as a sea region which shows the characteristics of the Pacific ocean, is separated from the Indian ocean by a distinctive rise.